Matrix metalloproteinase 9: A Representative Diagnostic Biomarker for Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis (Texas Journal of Medical Science, 2023)
Matrix metalloproteinase 9 is a proteolytic enzyme which is recently one of the more often studied biomarkers. Its possible use as a biomarker of neuronal damage in stroke, heart diseases, tumors, multiple sclerosis, and epilepsy is being widely indicated. In epilepsy, MMP-9 is suggested to play a role in epileptic focus formation and in the stimulation ofseizures. The increase of MMP- 9 activity in the epileptic focus was observed both in animal models and in clinical studies. MMP-9 contributes to formation of epileptic focus,for example, by remodeling ofsynapses. Its proteolytic action on the elements of blood-brain barrier and activation of chemotactic processes facilitates accumulation of inflammatory cells and induces seizures. Also, modification of glutamatergic transmission by MMP-9 is associated with seizures.